BIBLOS, slovenski servis za oddaljeno izposojo e-knjig - Zamida, Renata (Šolska knjižnica, 2016)
E-books do not need a special introduction in Slovenia; one fourth of the respondents in the latest national survey on reading and shopping habits stated that they were (also) readers of e-books. This trend is also present in Slovenian libraries, where, thanks to the Biblos e-book-lending platform, e-books have become a part of the regular offer of general libraries, and, according to statistical data, the demand for them is growing; in 2015, 30,000 e-books were lent through Biblos, which is 40 % more than the year before. The trend in the first three months of this year already indicates a similar growth in lending in 2016 as well. Users view the lending of e-books in libraries as some sort of copy of the procedures in the analogue world, only that they no longer have to walk to the library, since the service can be used anywhere and any time via an Internet interface, and is free of charge for library members.
Keywords: Biblos; bralne navade; branje; e-knjiga; e-knjižnica; elektronska izposoja; knjižnice